Réponses

2013-04-05T21:10:01+02:00

(5t - 2)(6t+9)=0

t=2/5

ou

t=-3/2

 

(3-2y)+(y+4)=0

(7-y)=0

y=7

 

2x(3x+2)(3x-1)=0

x=0

ou

x=-2/3

ou

x=1/3

 

 

(7-x)(x-7)=0

x=7

 

En espérant t'avoir aidé.

 

2013-04-05T21:16:08+02:00

3-2y = 0                    y+4 = 0

-2y = -3                     y = -4

y = -3/2

 

5t -2 = 0                     6t= -9

5t = +2                        t = -9/3

t = 2/5                         t = -3

 

2x= 0          3x +2= 0                3x=1

x=0              3x = -2                    x = 1/3

                    x = -2/3

 

7-x=0

-x = -7

x = 7